Comparing recovery community centers (RCCs) serving Black, Hispanic/Latino, and other communities: an exploratory secondary data analysis of a nationwide survey of RCC directors - Diadora DeCristofaro; Allison Futter; Alivia Williamson; Susanne S. Hoeppner; Lauren A. Hoffman; Marion J. Riggs; Judeline Joseph; Julia Ojeda; Amy A. Mericle; Vinod Rao; Philip X. Rutherford; Patty McCarthy; et al. (Frontiers in Public Health)
ObjectiveRacial and ethnic disparities exist in opioid-related overdose death rates and engagement with substance use disorder (SUD) treatment. Emerging peer recovery support services (PRSS) show promise in engaging and supporting marginalized populations. Recovery community centers (RCCs) are an important and growing source of community-based PRSS. Our goal was to examine if RCCs serving Black, Hispanic/Latino, or other racial/ethnic communities successfully engage marginalized populations in their community and if there are differences in the service models and functioning of RCCs serving different racial/ethnic communities.MethodsWe conducted exploratory secondary analyses of a nationwide survey of RCC directors (n = 122), in which directors described their RCC in terms of logistics, footprints, service model, linkages, services, and attitudes toward medication treatment. Analysis of variance and chi-square tests were used to compare RCCs serving different communities (i.e., Black, Hispanic/Latino, Other) on these variables, where “serving a Black/Hispanic/Latino community” was operationally defined as being in a ZIP code with more than double the national prevalence of Black (13.6%) and Hispanic/Latino (19.1%) individuals in the United States.ResultsOn average, the median [IQR] percentage of Black participants within RCCs serving Black communities was 45% [30–63%] (51% of residents in the RCCs' ZIP codes were Black); in RCCs serving Hispanic/Latino communities, 50% [28–60%] of RCC participants were Hispanic/Latino (57% of residents in the RCCs' ZIP codes were Hispanic/Latino). Across 70 variables describing the RCCs' service model and functioning, only two statistically significant differences emerged between RCCs serving Black, Hispanic/Latino, and other communities, using an alpha of 0.05. RCCs differed in offering 12-step mutual aid groups (lowest in RCCs serving Hispanic/Latino communities; p = 0.03) and the existence of direct collaboration with clinical sites providing medications for opioid use disorder (MOUD, most common in RCCs serving Black communities; p = 0.03).ConclusionThe overall RCC model appears to be consistent across racial/ethnic settings in terms of footprints, model of care, services offered, connection to relevant systems and organizations, and attitudes toward medications. Given the commonly observed racial/ethnic disparities in SUD care, the robustness of the RCC model across communities is promising.